Bone density measurements adjacent to acetabular cups in total hip arthroplasty using dual-energy CT: an in vivo reliability and agreement study. (August 2018) - Mussmann, Bo; Andersen, Poul Erik; Torfing, Trine; Overgaard, Søren
Background: Measuring bone mineral density (BMD) around acetabular prosthetic components with computed tomography (CT) is challenged by the complex anatomy and metal artifacts. Three-dimensional (3D) segmentation is required for the analysis, but it is usually not practically applicable on current CT workstations Purpose: To test the between-scan agreement and reliability of custom segmentation software for BMD measurements adjacent to cemented and uncemented acetabular cups in dual-energy CT (DECT). Material and Methods: Twenty-four male patients with total hip arthroplasty were scanned and rescanned using 130-keV virtual monochromatic DECT images. Hemispherical regions of interest were defined slice-by-slice and BMD was calculated around the acetabular cup using custom segmentation software. Results: In the uncemented cup, the mean BMD was 153 mg/cm 3 with a between-scan difference of 10 mg/cm 3 ( P < 0.0001). In the cemented cup, the mean BMD was 186 mg/cm 3 with a between-scan difference of 6 mg/cm 3 ( P = 0.15). In both uncemented and cemented cups the intraclass correlation coefficient between repeated measurements was >0.95 and narrow Bland–Altman Limits of Agreement. Conclusion: BMD can be measured with high absolute between-scan agreement and good reliability adjacent to acetabular cemented and uncemented cups using DECT and segmentation software.